Corporate credit risk modeling under carbon pricing uncertainty: A Knightian uncertainty approach - Chabi Marcellin Daki Dominique; Yixiang Tian (Sustainable Futures)
This study examines the financial implications of carbon pricing policies within the Knightian uncertainty framework. Employing a dynamic behavioural credit risk model driven by Lévy jump-diffusion, we scrutinise how carbon pricing uncertainty influences default probability and securities value. We explore investors' strategic responses to ambiguity and assess their impact on their investment decisions. Our findings reveal that carbon pricing uncertainty exacerbates the margin of default risk, has a moderating effect on stock value, and makes investors more cautious, thereby altering corporate capital structures. This study contributes to the discourse on carbon credit risk assessment and sustainable finance by addressing policy-driven uncertainties in the financial markets.